Active Listening untuk Meningkatkan Kapasitas Kepemimpinan Pengurus Yayasan Pemberdayaan Masyarakat Amungme dan Kamoro (YPMAK) Timika - Farida, Farida (LPPM Universitas Koperasi Indonesia, 2025)
This community service program aimed to enhance the leadership capacity of the elected board members of the Amungme and Kamoro Community Empowerment Foundation (YPMAK) in Timika through active listening training. The training was organized by Pusat Studi Pengembangan Bisnis dan Industri Kreatif (Pusdi-PBIK), Padjadjaran University, in collaboration with YPMAK and PT Freeport Indonesia, involving five elected board members. The training methods included lectures, discussions, role-playing, and evaluations, with materials covering the importance of active listening, its challenges, benefits, and practical techniques such as paraphrasing, maintaining eye contact, and avoiding interruptions. The results indicated active listening supports better decision-making, improves interpersonal relationships, and fosters trust. Challenges such as emotional and external noise, as well as the disparity between thinking speed and speaking speed, can be mitigated through effective communication techniques. It is concluded that active listening is an essential leadership skill that enables YPMAK board members to understand community needs, strengthen relationships with stakeholders, and enhance the success of empowerment programs. Implementing an organizational culture of active listening through advanced training and real-world simulation is recommended to ensure the sustainability of its positive impacts.